A Unifying Theory of Foreign Intervention in Domestic Climate Policy - Juan Moreno-Cruz; Anthony Harding (Center for Economic Studies and ifo Institute (CESifo), 2022)
We propose a theory of climate-policy motivated foreign intervention to study different forms of international climate governance in the presence of power imbalance. Foreign countries have at least three options to intervene in another country's domestic climate policy: i.) Agreements with Extraction; ii.) Agreements with Transfers; and iii.) Agreements with Sanctions. We distill the fundamental properties of different climate policy options into a simple parameterization and examine the incentivizes and preferences for each type of foreign intervention. We find that the preference for the type of foreign intervention depends critically on the policy externality of different domestic climate policies.
Keywords: Q54; Q55; C72; 330; climate change; mitigation; adaptation; geoengineering; international environmental agreements